Metformin blunts muscle hypertrophy in response to progressive resistance exercise training in older adults: A randomized, double‐blind, placebo‐controlled, multicenter trial: The MASTERS trial. Issue 6 (26th September 2019) - Walton, R. Grace; Dungan, Cory M.; Long, Douglas E.; Tuggle, S. Craig; Kosmac, Kate; Peck, Bailey D.; Bush, Heather M.; Villasante Tezanos, Alejandro G.; McGwin, Gerald; Windham, Samuel T.; Ovalle, Fernando; Bamman, Marcas M.; et al.
Abstract: Progressive resistance exercise training (PRT) is the most effective known intervention for combating aging skeletal muscle atrophy. However, the hypertrophic response to PRT is variable, and this may be due to muscle inflammation susceptibility. Metformin reduces inflammation, so we hypothesized that metformin would augment the muscle response to PRT in healthy women and men aged 65 and older. In a randomized, double‐blind trial, participants received 1, 700 mg/day metformin ( N  = 46) or placebo ( N  = 48) throughout the study, and all subjects performed 14 weeks of supervised PRT. Although responses to PRT varied, placebo gained more lean body mass ( p  = .003) and thigh muscle mass ( p  < .001) than metformin. CT scan showed that increases in thigh muscle area ( p  = .005) and density ( p  = .020) were greater in placebo versus metformin. There was a trend for blunted strength gains in metformin that did not reach statistical significance. Analyses of vastus lateralis muscle biopsies showed that metformin did not affect fiber hypertrophy, or increases in satellite cell or macrophage abundance with PRT. However, placebo had decreased type I fiber percentage while metformin did not ( p  = .007). Metformin led to an increase in AMPK signaling, and a trend for blunted increases in mTORC1 signaling in response to PRT. These results underscore the benefits of PRT in older adults, but metformin negatively impacts the hypertrophic response to resistance training in healthy older individuals. ClinicalTrials.gov Identifier: NCT02308228. Abstract : Because metformin reduces inflammation, we hypothesized that it would augment the muscle response to progressive resistance exercise training (PRT) in healthy older participants. Following 14 weeks of PRT, metformin blunted gains in lean mass, thigh muscle mass, and thigh muscle density compared to placebo. Metformin did not affect increases in muscle macrophage abundance. However, metformin increased AMPK signaling, leading to a reduced mean increase in mTOR signaling.